A novel membrane bioreactor for detoxifying industrial wastewater: II. Biodegradation of 3-chloronitrobenzene in an industrially produced wastewater. - Livingston,AG (Biotechnol Bioeng, 1993)
A novel membrane bioreactor has been used for the treatment of an industrially produced wastewater arising in the manufacture of 3-chloronitrobenzene. This wastewater is not amenable to direct biological treatment without some form pretreatment or dilution, due to the inorganic composition (pH <1, salt concentration 4% w/w) of the wastewater. In the membrane bioreactor, the organic pollutants are first separated from the wastewater by selective membrane permeation, and then biodegraded in the biological growth compartment of the bioreactor. At a wastewater flow rate of 64 mL h(-1) (corresponding to a contact time of approximately 1.7 hours) over 99% of the 3-chloronitrobenzene and over 99% of the nitrobenzene in the wastewater were degraded. Degradation of 3-chloronitrobenzene was accompanied by evolution of chloride ions in a stoichiometric ratio. Both 3-chloronitrobenzene and nitrobenzene degradation were accompanied by the evolution of carbon dioxide; approximately 80% of the carbon entering the system was oxidized to CO(2) carbon. Analysis of mass transport across the membrane revealed that 3-chloronitrobenzene and nitrobenzene are transported more rapidly than phenol. This is explained in terms of a resistances-in-series model, which shows phenol transfer to be rate limited by the membrane diffusion step, whereas the chloronitrobenzene and nitrobenzene transfer are rate limited by the liquid film mass transfer.